The Implementation of Thematic Development in Exposition Texts by EFL Learners - Williyan, Aldha; Sutopo, Djoko; Widhiyanto, Widhiyanto (English Education Journal, 2019)
The ability to implement the Thematic development is important in writing exposition text. Moreover, the exposition text is written to convince the readers. It means the writers are required to achieve the readers’ expectation. This study therefore aims to explore EFL learners’ exposition texts using Thematic progressions. The analysis of this element reveals the logical relations which become the main aspect in the text to achieve micro-level of coherence. Three exposition texts written by high, average and low proficiency level learners, are analyzed using systemic functional linguistics approaches on discourse analysis. The analysis reveals that the exposition text written by high proficiency level learner successfully implements the Thematic progressions and hence it achieves the micro-level of coherence. The Theme re-iteration patterns are implemented to keep the text focused. The zig-zag patterns are used to construct newly introduced information. Then, the multiple Theme patterns are implemented, especially in thesis statements of the texts, to preview the argument that will follow in the texts. Differently, the exposition text written by average proficiency level learner overuses one of the patterns, namely the Theme re-iteration patterns. This makes the text stuck in only same idea. However, the micro-level of coherence is still achieved as the logical relations of the text are still implemented successfully. Lastly, the exposition text written by low proficiency level learner unsuccessfully implements the Thematic progressions and hence the micro-level of coherence is not achieved. In sum, the implementation of Thematic progressions helps the texts to hang together and make sense.